Progressing intention progression: a call for a Goal-Plan Tree contest - Logan, Brian; Thangarajah, John; Yorke-Smith, Neil (2017)
User-supplied domain control knowledge in the form of hierarchically structured Goal-Plan Trees (GPTs) is at the heart of a number of approaches to reasoning about action. Reasoning with GPTs connects the AAMAS community with other communities such as automated planning, and forms the foundation for important reasoning capabilities, especially intention progression in Belief-Desire-Intention (BDI) agents. Research on GPTs has a long history but suffers from fragmentation and lack of common terminology, data formats, and enabling tools. One way to address this fragmentation is through a competition. Competitions are increasingly being used as a means to foster research and challenge the state of the art. For example, the AAMAS conference has a number of associated competitions, such as the Trading Agent Competition, while agent research is showcased at competitions such as RoboCup. We therefore issue a call for a Goal-Plan Tree Contest, with the ambition of drawing together a community and incentivizing research in intention progression.